2021
DOI: 10.1021/accountsmr.1c00193
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Protein Aggregation by Small Molecule-Based Colloidal Nanoparticles

Abstract: Conspectus Protein aggregation is associated with different human diseases such as Alzheimer’s, Huntington’s, Parkinson’s, diabetes type II, and cataracts. Currently no effective treatment exists for many of these diseases, particularly for neurological disorders. Ongoing research focuses on understanding the origin of protein aggregation, nucleation–growth mechanism of protein aggregation, origin of cytotoxicity of protein aggregates, cellular response of toxic protein aggregates, progress of diseases at intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
(232 reference statements)
1
13
0
Order By: Relevance
“…The development and accumulation of amyloidogenic proteins and lipoproteins correlated with the pathological events in neurodegenerative diseases, diabetes and related complications. As per the observations from this result, TNP inhibits the mechanism by which the confirmation of proteins got altered at the same time TNP also prevents the proteins from being getting aggregated under the influence of AGEs, especially with the glycation specific amino acids that is, arginine and lysine 44,45 …”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The development and accumulation of amyloidogenic proteins and lipoproteins correlated with the pathological events in neurodegenerative diseases, diabetes and related complications. As per the observations from this result, TNP inhibits the mechanism by which the confirmation of proteins got altered at the same time TNP also prevents the proteins from being getting aggregated under the influence of AGEs, especially with the glycation specific amino acids that is, arginine and lysine 44,45 …”
Section: Resultssupporting
confidence: 69%
“…As per the observations from this result, TNP inhibits the mechanism by which the confirmation of proteins got altered at the same time TNP also prevents the proteins from being getting aggregated under the influence of AGEs, especially with the glycation specific amino acids that is, arginine and lysine. 44,45 3.9 | Prevention of AGEs formation by TNP…”
Section: Ans-hydrophobicity Change Detection By Fluorescence Spectramentioning
confidence: 99%
“…In vitro studies have identified numerous potential alternatives to polyphenols for inhibiting amyloid formation based on in vitro studies [124][125][126], but their use in vivo is a challenge. Fortunately, there is a growing number of studies highlighting the loading of small molecules into nanoparticles, such as lipid vesicles or polymer-coated albumin aggregates [127][128][129][130][131]. This packaging improves the ability to cross the blood-brain barrier (for therapy) or penetrate biofilm (to combat functional amyloid), allowing the small molecules to target amyloidogenic monomers.…”
Section: Using Small Molecules and Polyphenols To Target Fuba And Bio...mentioning
confidence: 99%
“…Trehalose has been found to be effective in the treatment of different neurodegenerative pathologies including Alzheimer’s, Parkinson’s, and Huntington’s diseases. , Although the exact mechanism is not clear yet, it likely includes antiaggregation, anti-inflammation, and, in particular, autophagy induction, that is, the intracellular removal or destruction of unnecessary or dysfunctional components . Trehalose glycoclusters and nanocarriers were more efficient in delaying fibril formation and protein aggregation and protecting neurons than the small molecule trehalose, indicating that the cluster effect seen in stabilizing proteins with trehalose polymers is also applicable. Recently, poly­(trehalose) was also found to be effective in preventing Aβ peptide aggregation, part of the progression of Alzheimer’s disease.…”
Section: Applications Of Trehalose Materialsmentioning
confidence: 99%
“…As a small molecule, trehalose is a highly effective stabilizer and has been incorporated into polymers and other polymeric materials for even more dramatic stabilization results. 19 23 As our group has previously shown, in heat and lyophilization stability assays, proteins retain greater bioactivity in the presence of trehalose polymers (excipient, conjugate, hydrogel, or nanogel) than alone or with the same weight concentration of trehalose. 19 , 20 , 24 In the same vein, trehalose nanoparticles were better than trehalose alone at preventing proteins from undergoing fibrillation.…”
Section: Introductionmentioning
confidence: 99%